Mental health and life satisfaction of individuals with spinal cord injury and their partners 5 years after discharge from first inpatient rehabilitation. Issue 6 (June 2018) - Scholten, Eline W. M.; Tromp, Maria E. H.; Hillebregt, Chantal F.; Groot, Sonja; Ketelaar, Marjolijn; Visser-Meily, Johanna M. A.; Post, Marcel W. M.
Abstract Study design Cross-sectional study. Objectives To describe and compare mental health and life satisfaction between individuals with spinal cord injury (SCI) and their partners 5 years after discharge from first inpatient rehabilitation; and to examine if injury severity moderates the association between individuals' with SCI and their partners' mental health and life satisfaction. Setting Dutch community. Methods Sixty-five individuals with SCI and their partners completed a self-report questionnaire. Main outcome measures were the mental health subscale of the Short-Form Health Survey and the Life Satisfaction Questionnaire. Results Levels of mental health and life satisfaction of individuals with SCI and partners were similar, with median scores of 76 and 4.8 versus 76 and 4.6, respectively. Moderate to strong correlations between individuals with SCI and their partners were found for the mental health (r S = 0.35) and life satisfaction scores (r S = 0.51). These associations were generally stronger in the subgroup of individuals with less severe SCI. Associations between scores on separate life domains ranged from negligible (0.05) to moderate (0.53). Individuals with SCI and their partners were least satisfied with their 'sexual life'. Compared with their partners, individuals with SCI were significantly more satisfied in the domains 'leisure situation', 'partnership relation' and 'family life', and less satisfied in 'self-care ability'. Conclusions This study showed similarities but also differences in mental health and life satisfaction between individuals with SCI and their partners. In clinical practice, attention on mental health and life satisfaction should, therefore, focus on different domains for individuals with SCI and partners.